Geographical dsitribution of sago palm (metroxylon sagu rottb.) morphotypes and their genetic relationship based on chloroplast DNA RPS16 gene sequences prille Rose C. Vipinosa. - Vipinosa, Aprille Rose C. (2009)
Sago palm is considered as an important plant for food source and roofing materials by the lumads in Agusan Marsh. Wild stands of sago palms are mostly confined in large stands on Northern Mindanao particularly in Agusan Marsh. Being an ignored plant in the country, their geographical distributions in Mindanao, as well as their genetic variation need to be investigated. Results of this study revealed that the provinces of Agusan del Norte, Agusan del Sur, Surigao del Sur, Compostela Valley and Davao del Sur are home to diverse sago palms in the country. The exact locations of the sampling sites were obtained using the global positioning system. The environs of wild and semi-cultivated stands were characterized as swampy. The sago palm morphological types based on armature and petileo-rachis band patterns include the spineless brown, spineless gray, spineless blacked, spineless striped brown and white, spiny green and the two newly documented morphotypes namely the spiny white and spineless 3 brown bands. The isolated cpDNA rps 16 gene is approximately 980 bp. The purified DNA was subjected to plasmid cloning and the length of the sequenced products ranged from 845 to 858 bp. The aligned sequences had 794 bp with 100% homology. There was an absence of mutation detected among morphological types using this gene as a marker. The cpDNA rps 16 gene being a slow mutating gene connotes that several sago palms morphological types found in Midanao belong to a single species which is Metroxylon sagu. The DNA sequences in this study, upon comparison with the DNA sequence of M. salomonense available at the DNA databank is entirely synonymous with M. sagu. The base composition in cpDNA rps 16 gene of M. sagu and that of Cocos mucifera and Nypa fruticans showed high percent composition of adenine and low percentage of cytosine